Digital music collection for use with Music: an appreciation - Kamien, Roger (New York : McGraw Hill, 2011)
This CD contains audio files for 53 selections featured in Music: An Appreciation by Roger Kamien (6th Brief Edition and 9th Edition). In addition to the MP3 audio, this disc contains over 40 minutes of excerpts from three of the operas discussed in the textbook: Don Giovanni, La Boheme, and Wozzeck.
Keywords: Music -- Analysis, appreciation